MENINGKATKAN PRESTASI BELAJAR SISKOMDIG MEMPRODUKSI VIDEO MENGGUNAKAN METODE SMALL GROUP DISCUSSION MELALUI MEDIA INTERAKTIF ARTICULATED STORYLINE - APRILIANA WULANDARU (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2022)
The The purpose of this research is to improve the learning achievement of students in class X Mechatronics at vocational high school of SMK NEGERI 3 WONOSARI at the academic year 2021-2022. This class has 36 students by applying the Small Group Discussion learning method through the Articulated Storyline Interactive Learning Media (MPI). This classroom action research is designed in 2 cycles. Each cycle is carried out in 4 stages, namely planning, implementation, observation and reflection. The competency standards carried out the improvement plan for cycle 1 and cycle 2 are Produce Video in Simulation and Digital Communication (SISKOMDIG) subjects. The subject research is students who study in class X Mechatronics at SMK Negeri 3 Wonosari in the odd semester of the 2021/2022 academic year. The results of classroom action research show that the applying of the Small Group Discussion learning method through the Articulated Storyline Interactive Learning Media (MPI) can improve the learning outcomes of class X Mechatronics students at vocational high school of SMK Negeri 3 Wonosari in the 2021/2022 academic year. The result of average learning outcome in cycle 1 is 27 students who completed (75%) and increased in cycle 2. The students who completed became 34 students (94%). The average theory and practicale score of students is also increasing, from the pre-cycle average students theory score is 76.97 and the students practical score is 72.38 increasing in cycle 1 the students theory score of 78.75 while the students practical score is 74.58 and continues to increase in cycle 2 to , the student's theoretical score is 82.61 and the student's practical score is 80.97. Based on these percentages, it shows that learning by applying the Small Group X Mechatronics at SMK Negeri 3 Wonosari can increase learning outcome. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil prestasi belajar siswa kelas X Mekatronika SMK Negeri 3 Wonosari Tahun Pelajaran 2021-2022 yang berjumlah 36 siswa dengan menggunakan metode pembelajaran Small Group Discussion melalui Mediaa Pembelajaran Interaktif (MPI) Articulated Storyline. Penelitian tindakan kelas ini dirancang dalam 2 siklus. Setiap siklus dilaksanakan dalam 4 tahap, yaitu perencanaan, pelaksanaan, observasi dan refleksi. Adapun standar kompetensi yang dilakukan pada rencana perbaikan siklus 1 maupun siklus 2 yaitu Memproduksi Video pada mata pelajaran Simulasi dan Komunikasi Digital (SISKOMDIG). Subjek penelitian ini adalah siswa yang belajar di kelas X Mekatronika SMK Negeri 3 Wonosari pada semester ganjil tahun pelajaran 2021/2022. Hasil penelitian tindakan kelas menunjukan bahwa penggunaan metode pembelajaran Small Group Discussion melalui Mediaa Pembelajaran Interaktif (MPI) Articulated Storyline dapat meningkatkan hasil belajar siswa kelas X Mekatronika SMK Negeri 3 Wonosari Tahun Pelajaran 2021 / 2022, dengan rata - rata hasil belajar pada siklus 1 terdapat 27 siswa yang tuntas ( 75%) dan semakin meningkat pada siklus 2. Jumlah siswa yang tuntas menjadi 34 siswa ( 94% ). Rata - rata nilai teori dan nilai praktik siswa juga semakin meningkat, dari pra siklus rata - rata nilai teori siswa76.97 dan nilai praktik siswa 72.38 meningkat pada siklus 1 menjadi nilai teori siswa 78.75 sedangkan nilai praktik siswa 74.58 dan terus meningkat pada siklus 2 menjadi, nilai teori siswa 82.61 dan nilai praktik siswa 80.97. Berdasarkan prosentasi tersebut menunjukan bahwa pembelajaran menggunakan metode Small Group Discussion melalui MPI Articulated Storyline dapat meningkatkan minat belajar siswa untuk mempelajari materi Memproduksi video pada mata pelajaran Simulasi Komunikasi Digital (SISKOMDIG) yang berorientasi pada peningkatan hasil prestasi belajar siswa kelas X Mekatronika SMK Negeri 3 Wonosari.